Use of grass and leguminous species as winter mulching in organic notillage system of lettuce crop - Favarato, Luiz Fernando; de Souza, Jacimar Luis; Carvalho Guarçoni, Rogério; Tristão Alixandre, Fabiano; Abel Krohling, Cesar; Fornazier, Maurício José (Revista Ceres, 2023)
The no-tillage system for vegetables is an environmentally and economically suitable alternative, particularly for organic crops. However, further studies are needed using other plant species and under different growing conditions. This research aimed to evaluate the influence of different winter soil covers on lettuce development and yield under no-tillage system in an organic cultivation area. The experiment was arranged in a randomized block design with five treatments and six replications. The treatments used were three soil covers in the organic no-tillage system and two systems without cover crops and with soil tillage, one organic and the other conventional. The grass Avena strigosa (L.), the leguminous Lupinus albus (L.), and the intercropping of both species were used. The number of leaves per plant, stem length and diameter, head diameter, fresh and dry weight of plants, fresh weight of leaves and stem and Soil Plant Analysis Development (SPAD) index were evaluated. The use of leguminous straw is recommended for winter cultivation of lettuce in an organic no-tillage system. Black oat straw, single or intercropped, impaired the development and productivity of lettuce in the organic no-tillage system in winter cultivation.